Developing Instructional Skills: Perspectives of Feedback in Student Teaching - Noelle Won; Kimy Liu; Debra Bukko (Networks: An Online Journal for Teacher Research, 2019)
Feedback is essential for the transformation and development of new teachers. This action research study explored perceptions of feedback givers/receivers in the development of essential teaching skills in a new co-teaching model. Outcomes informed programmatic changes to teacher education trainings and protocols. The research team included teacher education faculty, including the program leader (author 1), faculty (author 2) and K-12 teacher leader (author 3). Student teachers (6), cooperating teachers (7), and university supervisors (3) participated in semi-standard interviews and close-ended surveys. Responses were analyzed for feedback content, frequency, timing, effectiveness, reception and application. Three key components of the feedback process were identified: Goals (What), Relationship (How), and Effect (Change). The relationship between the student teacher receiving and the supervisor providing the feedback significantly influenced student teacher perception and application of feedback. Resulting programmatic changes include cooperating teacher selection criteria, co-teaching training, regular triad team meetings, and rubric-based feedback protocols.
Keywords: action research; feedback; teacher education; field experiences; trust